Analisis Sistem Antrean sebagai Upaya Mengoptimalkan Layanan Teller di Bank BRI Cabang Cibadak Kabupaten Sukabumi - Agustian Suseno; Jauhari Arifin (Universitas Bunda Mulia, 2020)
High mobility in the era of globalization has resulted in the service system in a company being demanded to be faster to meet customer needs. Responsiveness or responsiveness is one aspect of service quality that serves as a benchmark in achieving customer satisfaction. Banking as a financial service in dealing with customers is closely related to the speed of services provided to customers, sometimes whether or not fast customers are constrained by unpredictable queuing times. BRI Bank as the bank that has the largest units that are spread almost all over Indonesia, BRI Bank has been committed to creating excellent service in serving its customers, so that the queuing system in a banking service is crucial to be noticed so that customers can be well served. The purpose of this study was to analyze the optimal teller service queue system for minimizing queue waiting time using queuing theory methods. Data collection with a determined time-based observation and recording of activities that occur directly by researchers to be carried out at BRI Cibadak Branch, Sukabumi. The data to be taken is the time to the teller the service queue system which is the time between the arrival of the customer and the time of customer service. The results showed an optimal number of tellers of 6 with an average server utilization of 67%, an average number in the queue of 0.57 customers, an average number in the system of 4.57 customers, an average time in the queue of 0.01 hours and an average time in the system of 0.11 hours.